Radical Prostatectomy: An Option for High-Risk Prostate Cancer - S. Rausch; C. Schmitt; T. Kälble (Advances in Urology)
Introduction. High-risk prostate cancer represents a therapeutic challenge. The role of radical prostatectomy (RP) in patients with extreme PSA values is under discussion. Material and Methods. We retrospectively analysed our data of 56 consecutive patients with preoperative PSA ≥ 40 mg/mL undergoing open radical retropubic prostatectomy from 1999 to 2009. Patient survival and time to PSA recurrence were recorded, and the Kaplan-Meier survival analysis was performed. Postoperative quality of life and functional status were investigated using a SF-12 questionnaire and determining the number of pads used per day. Results. Overall 56 patients were available for followup after a median time of 83.84 months. Locally advanced carcinoma was present in 84% while 16% of patients had organ-confined stages. A positive nodal status was observed in 46%. Overall survival was 95% at five and 81% at 10 years. Cancer-specific survival was 100% for five years and 83% for 10 years. Corresponding biochemical recurrence-free survival was low (52% and 11%, resp.). Quality of life and functional outcomes were favourable. Conclusions. In patients with PSA ≥ 40 mg/mL, RP allows long-term control, exact planning of adjuvant treatment, and identification of curable disease.